XIX դարի վերջի և XX դարի սկզբի կավճաներկի հայ վարպետները - Ավետիսյան, Ա. Ս. (Մանկավարժ հրատ․)
Հայ արվեստում քիչ չեն կավճաներկով ստեղծագործած արվեստագետների անունները. Հովսեփ և Սեպուհ Մանասներ, Վիգեն Աբդուլահ (Վիչեն, Վենսան Աբդուլլահյան), Ենոք Նազարյան, Արսեն Շաբանյան, Էդգար Շահին, Փանոս Թերլեմեզյան և այլոք: Նրանք կիրառելի դարձնելով կավճաներկի տեխնիկան դարձել են հայ իրականության մեջ այդ ոճի առաջնեկները: Հոդվածում անդրադարձ է կատարվել կավճաներկի տեխնիկային և համաշխարհային կերպարվեստի պատմությունից բերվել են օրինակներ տվյալ նյութով աշխատած արվեստագետներից: Ներկայացված են հայազգի նկարիչների կավճաներկով կատարված ստեղծագործությունները, տրվել են դրանց բնութագրական կողմերը: В армянском искусстве немало мастеров, пишущих мелом: Овсеп и Сепух Манаснер, Виген Абдулла (Вичен, Венсан Абдуллахян), Енок Назарян, Арсен Шабанян, Эдгар Шахин, Панос Терлемезян и другие видные мастера. Применяя технику рисования мелом, они стали первыми, кто писал в этом стиле. В статье говорится о технике рисования мелом, приводятся примеры художников, работавших с материалом из истории мирового изобразительного искусства. Речь идет о работах армянских художников, выполненных мелом, даны их описательные аспекты. There are many names of artists created with chalk in Armenian art. Hovsep and Sepuh Manas, Vigen Abdullah (Vichen, Vensan Abdullahyan), Yenok Nazaryan, Arsen Shabanyan, Edgar Sahin, Panos Terlemezyan and some other prominent artists as well. By making the chalk painting technique applicable, they became the first of its kind in the Armenian reality The article refers to the technique of chalk painting, citing examples from the artists who worked with the material from the history of world fine arts. We are talking about the works of Armenian painters made of chalk and introducing their descriptive aspects. One of the best portrait painters of Armenian fine arts, Yenok Nazaryan (1869-1928), painted with chalk. We learn about the artist mainly from the testimonies of contemporaries from several articles published in periodicals. Nazaryan from Constantinople He got acquainted with the technique of chalk painting after graduating from the local College of Fine Arts, during his studies in Italy 4, later becoming an unsurpassed master of chalk painting in the Armenian reality. He lived in Tbilissi (Georgia) and then left for Alexandropol at the invitation of the mayor of Alexandropol (who wanted to order his parents' masks). For a short time he headed the local painting studio
Keywords: Արվեստ